2017
DOI: 10.1186/s12917-017-1144-y
|View full text |Cite
|
Sign up to set email alerts
|

The practical use of genome sequencing data in the management of a feline colony pedigree

Abstract: BackgroundA higher prevalence of inherited disorders among companion animals are often rooted in their historical restricted artificial selection for a variety of observed phenotypes that eventually decreased genetic diversity. Cats have been afflicted with many inherited diseases due to domestication and intense breed selection. Advances in sequencing technology have generated a more comprehensive way to access genetic information from an individual, allowing identification of putative disease-causing variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
2
0
0
Order By: Relevance
“…We suggest that the reasons for identifying shorter ROH relies on the higher resolution of WGS data in comparison with SNPchip data. This difference in ROH calling was also observed in another study with feline that used both types of dataset for the same individuals [46].…”
Section: Discussionsupporting
confidence: 58%
“…We suggest that the reasons for identifying shorter ROH relies on the higher resolution of WGS data in comparison with SNPchip data. This difference in ROH calling was also observed in another study with feline that used both types of dataset for the same individuals [46].…”
Section: Discussionsupporting
confidence: 58%
“…We suggest that the reasons for identifying shorter ROH relies on the higher resolution of WGS data in comparison with SNPchip data, leading to an identification of two or more ROH (using WGS data) as a unique ROH. This difference in ROH calling was also observed in another study with feline that used both types of dataset of the same individuals[46].It is also important to highlight that low coverage WGS data may present higher error rate of variant calling in comparison with SNPchip data and that it may lead to inaccuracy of ROH calling[29]. Thus, we followed parameters based on Ceballos et al[29], which demonstrated equivalent results to SNPchip data's results, when dealing with low coverage WGS, considering the differences of error rate in variant calling in both types of data.…”
supporting
confidence: 67%